Intestinal absorption of cholecalciferol in alcoholic liver disease and primary biliary cirrhosis. Issue 7 (July 1979) - Barragry, J M; Long, R G; France, M W; Wills, M R; Boucher, B J; Sherlock, S
Abstract : The intestinal absorption of (3H)cholecalciferol was studied in five patients with alcoholic liver disease, six patients with primary biliary cirrhosis, and 15 healthy subjects. The rate of appearance in plasma of (3H)cholecalciferol after oral ingestion and the subsequent appearance of (3H) polar metabolites in the alcoholic subjects were similar to those in the healthy subjects. In subjects with primary biliary cirrhosis the rate of appearance in plasma of (3H)cholecalciferol was significantly reduced. The rate of appearance of labelled polar metabolites of cholecalciferol was also lower in this group, suggesting that increased removal of labelled vitamin by conversion into more polar metabolites could not account for the reduced plasma (3H)cholecalciferol response. It is suggested that intestinal absorption of cholecalciferol is usually normal in alcoholic liver disease but impaired in primary biliary cirrhosis. Hepatic 25-hydroxylation is normal in alcoholic liver disease but may be defective in primary biliary cirrhosis.